2002
DOI: 10.1523/jneurosci.22-20-08911.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Induces a PI3-Kinase-Independent Activation of Akt in Striatal Neurons: A New Route to cAMP Response Element-Binding Protein Phosphorylation

Abstract: Akt is classically described as a prosurvival serine/threonine kinase activated in response to trophic factors. After activation by phosphoinositide 3-kinase (PI3-kinase), it can translocate to the nucleus where it promotes specific genetic programs by catalyzing phosphorylation of transcription factors. We report here that both dopamine (DA) D1 (SKF38393) and D2 (quinpirole) agonist treatments rapidly increase, in primary striatal neurons in culture, phosphorylation levels of Akt on Thr 308 , a residue that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
160
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 56 publications
(78 reference statements)
17
160
4
Order By: Relevance
“…This observation is also consistent with data obtained from DAT-KO mice in which DA receptors are continuously stimulated. In this regard, our results differ from previous reports of a D2 receptor activation of Akt and inactivation of GSK-3␤ after short-term exposure of cell cultures to DA agonists (40)(41)(42) or within 15 min after treatment of mice with cocaine (40) or amphetamine (43). Further detailed studies of DA receptor signaling at different time points after stimulation will be necessary to explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is also consistent with data obtained from DAT-KO mice in which DA receptors are continuously stimulated. In this regard, our results differ from previous reports of a D2 receptor activation of Akt and inactivation of GSK-3␤ after short-term exposure of cell cultures to DA agonists (40)(41)(42) or within 15 min after treatment of mice with cocaine (40) or amphetamine (43). Further detailed studies of DA receptor signaling at different time points after stimulation will be necessary to explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…5c). It has been previously shown that CREB is a regulatory target for the protein kinase Akt (23)(24)(25)(26)(27). In this way we show that myr-Akt induces notably the activity of a CRE-luciferase reporter transfected to Schwann cells (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…downstream target of Akt (22)(23)(24)(25)(26)(27). However, we also found that the deletion of the CRE in the HMGR reductase promoter did not reduce the myr-Akt-dependent transcriptional activity (Fig.…”
Section: Intracellular Pathways Involved In Neuregulin 1 Signaling-mentioning
confidence: 57%
“…Striata were dissected out from 14-d-old Swiss mouse embryos (Janvier, France) and prepared as previously described (Brami-Cherrier et al, 2002). Cells were suspended in Neurobasal medium supplemented with B27 (Invitrogen, Cergy Pontoise, France), 500 nM L-glutamine, 60 g/ml penicillin G and 25 M ␤-mercaptoethanol (Sigma, L'Isle d'Abeau, Chasnes, France) and plated into 24-well (1.8 ϫ 10 5 cells per well) or 6-well (8.6 ϫ 10 5 cells per well) Nunc (Dutscher, Brumath, France) multiwell plates coated with 50 g/ml poly-D-lysine (Sigma).…”
Section: Methodsmentioning
confidence: 99%